Α new tropical invader in Greece: The lantana plume moth Lantanophaga pusillidactylus (Lepidoptera: Pterophoridae) - Demetriou, Jakovos; Kazilas, Christos; Koutsoukos, Evangelos; Kalaentzis, Konstantinos (ENTOMOLOGIA HELLENICA, 2020)
This study documents the first known record of the lantana plume moth Lantanophaga pusillidactylus (Walker, 1864) in Greece. The moth was observed in four localities from April 2018 to November 2019, and four individuals were collected and deposited in the Zoological Museum of the University of Athens (ZMUA). All specimens were identified as L. pusillidactylus, an alien species in Europe, that has been recently introduced in Spain, Italy (Sicily), Portugal, and Malta. The possible pathways of its introduction, as well as potential ecological implications, are discussed.